(untitled) (Medical Forum Monthly, 2020)
Objective: To isolate the presence of Staphylococcus. aureus from different operation theaters and confirmation by the help of PCR and to determine the antibiotic susceptibility pattern by disk diffusion method. Study Design: Clinical Study Place and Duration of Study: This study was conducted at the Institute of Microbiology and Biotechnology Department, University of Lahore, Pakistan from September 2016 to March, 2017. Materials and Methods: To evaluate contamination in various operation theaters from Tertiary Care Hospital at Lahore city. Air contamination of operation theatre was evaluated by settle plate method. Petri plates containing media were opened on different places that include window, instrument table, and entrance and OT table for about 15 minutes. Total 12 media containing petri plates were opened at different levels in each operation theatre and incubated for 24 hours at 37̊ϲ.Antibiotic susceptibility done by disk diffusion method and molecular identification was also done. Results: To detect antimicrobial resistance, mecA and vanA gene were amplified and molecular identification of S.aureus was done by TStaG gene.14 out of 16 samples were positive for TStaGgene, 8/8 were positive for mecA and 0/7 for vanA gene. Conclusion: S.aureus is commonly present in all operation theatres and causes a lot of lethal infections thus proper sterilization/disinfection and proper antibiotic selection is required for its treatment.